Nbn and atm cooperate in a tissue and developmental stage-specific manner to prevent double strand breaks and apoptosis in developing brain and eye - Rodrigues, Paulo M. G.; Grigaravicius, Paulius; Remus, Martina; Cavalheiro, Gabriel R.; Gomes, Anielle L.; Martins, Mauricio R.; Frappart, Lucien; Reuss, David; McKinnon, Peter J.; Deimling, Andreas von; Martins, Rodrigo A. P.; Frappart, Pierre-Olivier (PLOS ONE, 2013)
Nibrin (NBN or NBS1) and ATM are key factors for DNA Double Strand Break (DSB) signaling and repair. Mutations in NBN or ATM result in Nijmegen Breakage Syndrome and Ataxia telangiectasia. These syndromes share common features such as radiosensitivity, neurological developmental defects and cancer predisposition. However, the functional synergy of Nbn and Atm in different tissues and developmental stages is not yet understood. Here, we show in vivo consequences of conditional inactivation of both genes in neural stem/progenitor cells using Nestin-Cre mice. Genetic inactivation of Atm in the central nervous system of Nbn-deficient mice led to reduced life span and increased DSBs, resulting in increased apoptosis during neural development. Surprisingly, the increase of DSBs and apoptosis was found only in few tissues including cerebellum, ganglionic eminences and lens. In sharp contrast, we showed that apoptosis associated with Nbn deletion was prevented by simultaneous inactivation of Atm in developing retina. Therefore, we propose that Nbn and Atm collaborate to prevent DSB accumulation and apoptosis during development in a tissue- and developmental stage-specific manner.
Gesehen am 01.02.2022